EGCG protects endothelial cells against PCB 126-induced inflammation through inhibition of AhR and induction of Nrf2-regulated genes - Han, Sung Gu (2012)
Tea flavonoids such as epigallocatechin gallate (EGCG) protect against vascular diseases such as atherosclerosis via their antioxidant and anti-inflammatory functions. Persistent and widespread environmental pollutants, including polychlorinated biphenyls (PCB), can induce oxidative stress and inflammation in vascular endothelial cells. Even though PCBs are no longer produced, they are still detected in human blood and tissues and thus considered a risk for vascular dysfunction. We hypothesized that EGCG can protect endothelial cells against PCB-induced cell damage via its antioxidant and anti-inflammatory properties. To test this hypothesis, primary vascular endothelial cells were pretreated with EGCG, followed by exposure to the coplanar PCB 126. Exposure to PCB 126 significantly increased cytochrome P450 1A1 (Cyp1A1) mRNA and protein expression and superoxide production, events which were significantly attenuated following pretreatment with EGCG. Similarly, EGCG also reduced DNA binding of NF-κB and downstream expression of inflammatory markers such as monocyte chemotactic protein-1 (MCP-1) and vascular cell adhesion protein-1 (VCAM-1) after PCB exposure. Furthermore, EGCG decreased endogenous or base-line levels of Cyp1A1, MCP-1 and VCAM-1 in endothelial cells. Most of all, treatment of EGCG upregulated expression of NF-E2-related factor 2 (Nrf2)-controlled antioxidant genes, including glutathione S transferase (GST) and NAD(P)H:quinone oxidoreductase 1 (NQO1), in a dose-dependent manner. In contrast, silencing of Nrf2 increased Cyp1A1, MCP-1 and VCAM-1 and decreased of GST and NQO1 expression, respectively. These data suggest that EGCG can inhibit AhR regulated genes and induce Nrf2-regulated antioxidant enzymes, thus providing protection against PCB-induced inflammatory responses in endothelial cells.